THE ROLE OF PROVIDING AN EXPLANATION WITHIN THE CONTEXT OF EMAILED APOLOGIES: A CROSS-CULTURAL APPROACH - Tania Walker (Italiano LinguaDue)
This article explores differences in the realisation of one apology strategy between Australian learners of Italian, native speakers of Italian and native speakers of Australian English.  The strategy in question is providing an explanation, which is here investigated through an analysis of elicited emails addressed to academic staff at university.  The analysis demonstrates that while Australian learners of Italian tend to resort to this strategy as an obligatory stage in the performance of apologies, native Italian speakers frequently omit it. Such difference between the two groups is further explored through interview data and fieldnotes which present participants’ perceptions of providing an explanation, which yield insights into the rationale underlying such choices of constructing and/or omitting explanations in order to account for offences. The findings from all analyses evidence the highly contextualised nature of the speech act of apology, highlighting the Australian and Italian students’ diverse understandings of the different institutional roles of professors and tutors in their respective cultural and institutional contexts.